Changes in the structure, perfusion, and function of the hippocampus in type 2 diabetes mellitus - Li, Mingrui; Li, Yifan; Zhao, Kui; Tan, Xin; Chen, Yuna; Qin, Chunhong; Qiu, Shijun; Liang, Yi (Frontiers in Neuroscience, 2023)
Abstract Objective: This study aims to analyze the changes in the structure, perfusion, and function of the bilateral hippocampus in type 2 diabetes mellitus (T2DM) by multimodal MRI imaging, hoping to clarify the potential neural mechanism of hippocampus-related brain injury in T2DM. Methods: We recruited 30 T2DM patients and 45 healthy controls (HCs), who were performed 3D-T1, resting-state functional MRI (rs-fMRI) , arterial spin labeling (ASL) sequences and a series of cognitive tests. Then, we compared the differences of two groups in the cerebral blood flow (CBF) value, amplitude of low-frequency fluctuation (ALFF) value, fractional ALFF (fALFF) value, coherence-based regional homogeneity (Cohe-ReHo) value and degree centrality (DC) values of the bilateral hippocampus and the functional connectivity (FC) between the bilateral hippocampus and all brain voxels. Results: In the T2DM group, the bilateral hippocampal volume and the CBF value of the right hippocampus were lower than those in the HCs, and the ALFF value, fALFF value and Cohe-ReHo value of the bilateral hippocampus were higher than those in the HCs. Correlation analysis showed that FBG was negatively correlated with the residuals of left hippocampal volume (r=-0.407, P =0.025) and right hippocampal volume (r=-0.420, P=0.021). Conclusion: This study indicate that the volume and perfusion of the hippocampus are decreased in T2DM patients that may be related to microvascular dysfunction and vascular damage due to chronic hyperglycemia. Local spontaneous neural activity and coordination are increased in the hippocampus of T2DM patients, possibly as an adaptive compensation for cognitive decline.